Biocontrol of gray spot disease on Polygonatum cyrtonema Hua by Bacillus velezensis GX1 - L. Sun; G.L. Deng; H.L. Wu; Q. He; S.H. Hu; J.Y. Li; X.Y. Li; S. Meng; A.N. He; Y.Q. Tian; X. Chen; S.H. Li (Biological Control)
This study evaluated the biocontrol efficacy of Bacillus velezensis GX1 against gray spot disease (Pestalotiopsis xuefengensis) on the horticultural species, Polygonatum cyrtonema Hua. Results indicated that GX1 effectively inhibited P. xuefengensis HJHB1, inhibiting growth of the pathogen by 74.97 % in vitro and inhibiting disease development by 87.13 % in field experiments. Notably, a 10 % (v/v) concentration of cell-free supernatant (CFS) of GX1 fully inhibited mycelial growth. An extract of lipopeptides (LPs) prepared at 60 μg/ml strongly inhibited mycelial growth and spore germination and caused morphological deformation of the mycelia. Liquid chromatography-tandem mass spectrometry (LC-MS/MS) analysis revealed that strain GX1 produced significantly higher levels of surfactin A, surfactin B and plipastatin, relative to strain GX8, an ineffective strain. Commercial preparations of plipastatin and surfactin indicated that plipastatin exhibited strong antifungal activity but surfactin did not. A bacterial solution of GX1 had no significant effect on superoxide dismutase (SOD) activity in P. cyrtonema but did enhance the activity of peroxidase (POD) and decreased catalase (CAT) activity, which are associated with increased resistance of P. cyrtonema to gray spot disease.